2020
DOI: 10.1038/s41589-020-0640-8
|View full text |Cite
|
Sign up to set email alerts
|

MYPT1 O-GlcNAc modification regulates sphingosine-1-phosphate mediated contraction

Abstract: Many intracellular proteins are modified by N-acetylglucosamine, a posttranslational modification termed O-GlcNAc. This modification is found on serine and threonine side-chains and has the potential to regulate signaling pathways through interplay with phosphorylation. Here, we discover and characterize one such example. We find that O-GlcNAc levels control the sensitivity of fibroblasts to actin contraction induced by the signaling lipid sphingosine-1-phosphate (S1P), culminating in the phosphorylation of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
4
22
0
Order By: Relevance
“…These results are highly consistent with the timing of cellular contraction and the fact that the NIH3T3 cells will eventually return to a relaxed state. Again, this supports the model built upon our published S1P data ( 26 ) where non- O -GlcNAc-modified MYPT1 can be phosphorylated and deactivated by ROCK ( Fig. 3 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These results are highly consistent with the timing of cellular contraction and the fact that the NIH3T3 cells will eventually return to a relaxed state. Again, this supports the model built upon our published S1P data ( 26 ) where non- O -GlcNAc-modified MYPT1 can be phosphorylated and deactivated by ROCK ( Fig. 3 ).…”
Section: Resultssupporting
confidence: 89%
“…In our previous publication ( 26 ), we showed that MYPT1 is heavily O -GlcNAc modified at multiple sites in a serine/threonine-rich region located between residues 550 and 600. We also found that deletion of this entire region, yielding a protein we term MYPT1Δ, was required to notably reduce the overall O -GlcNAc levels but did not adversely affect MYPT1 phosphatase activity against MLC.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…O-GlcNAc modifications are catalyzed by OGT and removed by OGA, which utilizes UDP-GlcNAc, the final product of the HBP pathway as its substrate. Recent studies suggested that O-GlcNAcylation modulates the function of numerous proteins under both physiological and pathological conditions, emerging as a key mediator of many cardiovascular pathophysiological processes [ [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. Upregulation of HBP and increased O-GlcNAc modification have been shown to be protective against acute I/R injury in previous studies by ourselves and others [ 26 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost concomitantly, Pedowitz et al ( 21 ) also studied MYPT1 O-GlcNAcylation. They unraveled that under basal conditions it antagonizes pT696, which is an inhibitory phosphorylation for the myosin phosphatase, and controls actin contraction.…”
Section: O-glcnac Governs Centrosomal Distancesmentioning
confidence: 99%